Pixelated Egg Digital Ventures - Pai, Madhura (ATLAS SkillTech University, 2024)
My time at Pixelated Egg Digital Venture was a rewarding experience that included a wide range of tasks and responsibilities, all of which contributed to my thorough expertise of digital marketing and content management. This expanded executive brief emphasises the different experiences and knowledge I gained while working at the agency.I began my journey by diving into the field of content curation for well-known businesses like Jeevansaathi and First Naukri. This first position was crucial in defining my content production talents, as I learned how to create interesting and personalised material for numerous social media platforms. In this work, I learned how to connect with specific target audiences, adapt to their tastes, and maintain brand consistency throughout digital campaigns. As my article curation abilities improved, I progressively broadened my horizons to include competition research for Zed Anmol. This position requires a thorough understanding of market dynamics, competitive strategies, and consumer behaviour analysis. By learning about our competitors' strengths and shortcomings, I was able to contribute strategically to helping our customers surpass their competition in the highly competitive digital world. The formulation of complete content calendars for our portfolio's smaller businesses was a crucial milestone in my path. This complicated undertaking required rigorous preparation and organisation to ensure each brand's harmonic and consistent online presence. Over time, I grew skilled at organising and scheduling content to maximise interaction and maintain each brand's own voice. Recognising the value of thought leadership in the business, I decided to contribute to the agency's blog. This forum provided me with the opportunity to discuss market insights, new trends, and novel methods. It not only demonstrated our firm's knowledge, but it also established us as a vital resource, creating confidence and credibility among our clients and colleagues. Client service was fundamental to my duties, and I diligently supervised the reporting process for our diversified clients. This entailed strategically arranging social media material to ensure that our clients' messages reached their target audiences at times when online activity was at its height. I continuously increased our clients' online engagement numbers by using a data-driven strategy.In addition to client-focused activities, I actively participated in comprehensive research to uncover new clients to whom we might pitch our services. In-depth market analysis, competition evaluations, and trend identification were all part of this research. Tailoring our pitches to the individual demands of prospective customers was critical in increasing our client base and contributing to the agency's success. Conducting social media audits, which involved a detailed review of our client's social media accounts, became another essential component of my position. This critical analysis allowed me to identify strengths and flaws before developing tactics to improve their online presence, engagement, and reach. To broaden my skill set, I experimented with optimising Google Business Profiles to increase our clients' presence in local search results. Managing and improving their online image became a critical component in increasing traffic, conversions, and, eventually, brand awareness and consumer confidence. In addition, I actively participated in debates and contributed to the development of content across several digital channels. This interactive training deepened my grasp of future trends, industry best practices, and the ever-changing dynamics of the digital ecosystem. My time with Pixelated Egg Digital Venture was a fast-paced, varied, and transformational journey of constant learning and growth. It gave me a well-rounded skill set that included content development, social media management, digital marketing tactics, customer service, and industry knowledge.
Project Report on Pixelated Egg Digital Ventures (2022-24) Under the Guidance of Dr. Vinima Gambhir